Development of a Project Based Learning STEM Learning Tool to Enhance Scientific Communication Skills and Learning Outcomes in Engineering and Technology Topic - Wardani, Diana Widyaningtyas; Putra*, Pramudya Dwi Aristya; Gunawan, Arvidhea Safira; Lesmono, Albertus Djoko; Siswati, Bea Hana; Bunyamin, Muhammad Abd Hadi (Jurnal IPA & Pembelajaran IPA, 2025)
Improving students scientific communication skills in the learning process has become a recent challenge. Scientific communication is one of the essential skills required, particularly in science education. The purpose of this research was to develop a learning tool of project based learning-science, technology, engineering, and mathematics (PjBL-STEM) to improve scientific communication skills and learning outcomes of the grade XII students on the topic of engineering and technology. This research employed a research and development (RD) method through 4-D model approach (define, design, develop, and disseminate). The study involved students of SMAN 5 Jember to implement a small (N=30) and large-scale (N=60) for this research. The research instruments of this study were expert validation, teacher and student response questionnaires, learning outcome tests, and scientific communication skills test. Expert validation showed that the learning tools (teaching instructional design, student worksheets, learning materials, and assessments) were excellent, with an average score above 4.0. Practicality tests by teachers and students confirmed the usefulness of this tool, categorizing it as "very practical" to "practical". In addition, the device significantly improved students' scientific communication skills (significance values of 0.001 and 0.000) and learning outcomes (mean scores of 77.43 for the small group and 77.35 for the large group). This study concludes that the developed PjBL-STEM device is feasible, practical, and effective in supporting 21st-century learning